2017
DOI: 10.1177/0148607116673185
|View full text |Cite
|
Sign up to set email alerts
|

Underweight Status Is an Independent Predictor of In‐Hospital Mortality in Pediatric Patients on Extracorporeal Membrane Oxygenation

Abstract: Underweight status was an independent predictor for in-hospital mortality in our cohort of pediatric ECMO patients. Prospective studies evaluating the impact of metabolic state of children on ECMO should further define this relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 36 publications
1
42
1
Order By: Relevance
“…Although undernutrition in critically ill children, and more specifically in children requiring ECMO support, has been associated with a poor prognosis ( 6 8 ), in our study, undernutrition was not associated with higher mortality or more gastrointestinal problems. Only children who needed prolonged ECMO support had more complications as reflected in the multivariable study.…”
Section: Discussioncontrasting
confidence: 72%
“…Although undernutrition in critically ill children, and more specifically in children requiring ECMO support, has been associated with a poor prognosis ( 6 8 ), in our study, undernutrition was not associated with higher mortality or more gastrointestinal problems. Only children who needed prolonged ECMO support had more complications as reflected in the multivariable study.…”
Section: Discussioncontrasting
confidence: 72%
“…Anton‐Martin et al, showed in a retrospective single center review of 20 years and 491 pediatric ECMO patients, that 24% of their patients were underweight which was independently associated with increased mortality with an odds ratio (OR) of 2 . In a retrospective review of the PHIS database, the use of inhaled nitric oxide (iNO) during ECMO treatment was evaluated .…”
Section: Discussionmentioning
confidence: 99%
“…Deleterious effects from overfeeding and underfeeding are well-documented. Malnutrition is reported to be associated with poor wound healing ( 5 ), loss of myocardial mass ( 6 ), and increased mortality ( 7 ), whilst excess nutrition has been found to be associated with steatosis and liver dysfunction ( 8 ). As such, optimization of nutrition is vital in the management of pediatric patients on ECMO.…”
Section: Introductionmentioning
confidence: 99%